Pendampingan Penyusunan Laporan Keuangan Primkoppol Resor Kota Pekalongan - Sutrisno, Catur Ragil; Mahmudah, Dina Amalia; Kushermanto, Andi; Agustina, Dwi (LPPM Universitas Pekalongan, 2026)
The financial statement preparation assistance program at PRIMKOPPOL Resor Kota Pekalongan for the 2024 fiscal year aimed to strengthen the management’s capacity in understanding and applying the Financial Accounting Standards (SAK) as regulated by the Permenkop No. 2 Tahun 2024. Conducted over two weeks, the program included stages of coordination, planning, analysis, and correction of the cooperative’s financial reports and performance. The results indicate that PRIMKOPPOL’s financial statements were prepared with greater transparency and accountability, though improvements are still needed in the cash flow and equity change reports. These results demonstrate that the cooperative maintains sound financial performance, efficiently manages its assets, and possesses strong financial resilience. The assistance program successfully enhanced the accountability and professionalism of the cooperative’s management in preparing financial statements in accordance with accounting standards.